Genome-Wide Identification, Phylogeny, and Expression Profile of the Dmrt (Doublesex and Mab-3 Related Transcription Factor) Gene Family in Channel Catfish (Ictalurus punctatus) - Xu, Siqi; Zhang, Shiyong; Zhang, Wenping; Liu, Hongyan; Wang, Minghua; Zhong, Liqiang; Bian, Wenji; Chen, Xiaohui (Frontiers in Genetics, 2022)
The Dmrt (Doublesex and Mab-3 related transcription factor) gene family is a class of crucial transcription factors characterized by a conserved DM domain related to sex determination and differentiation, which has been systematically described in various teleost fish, but less so in channel catfish, an important global aquaculture species in the US and China. In this study, seven Dmrt genes from channel catfish genome were identified and analyzed using bioinformatics methods. Seven IpDmrt genes were distributed unevenly across five chromosomes. Synteny analysis revealed that Dmrt1, Dmrt2a, Dmrt2b, Dmrt3, Dmrt4, and Dmrt5 were relatively conserved in teleost fish. Tissue distribution analysis showed that IpDmrt1, IpDmrt2b, IpDmrt5, and IpDmrt6 exhibited sexually dimorphic expression patterns and, among them, IpDmrt1 and IpDmrt6 had high expression levels in the testes, while IpDmrt2b and IpDmrt5 had more significant expression levels in the ovaries than in other tissues. After 17β-estradiol treatment, IpDmrt2b and IpDmrt5 were significantly up-regulated, while the expression of IpDmrt1 and IpDmrt6 was significantly repressed in XY channel catfish ovaries compared with XX channel catfish ovary. The present study provides a comprehensive insight into the Dmrt gene family of channel catfish. The results suggest that IpDmrt1 and IpDmrt6 may play an important role in testis differentiation/development, while IpDmrt2b and IpDmrt5 are critical in ovary development in this species.